Case report: Usefulness of angioscopy in determining antiplatelet drug reduction after carotid artery stenting - Fukutome, Kenji; Shiba, Mikio; Aketa, Shuta; Mitsui, Takaaki; Shiraishi, Yuki; Hayami, Hiromichi; Murakami, Yasutaka; Matsuoka, Ryuta; Tei, Rinsei; Shin, Yasushi; Motoyama, Yasushi (Frontiers in Neurology, 2023)
We report a case in which neointima was confirmed by angioscopy and antiplatelet drug administration was reduced 2 months after carotid artery stenting (CAS). A patient in their 80s was scheduled to undergo resection for renal cancer; however, he also had right cervical internal carotid artery stenosis. Because this was a risk for general anesthesia, CAS was performed after first starting dual antiplatelet therapy. Urologically, early reduction of antiplatelet drugs was necessary for a nephrectomy. Although no obvious neointima could be identified on ultrasound 2 months after CAS, thin neointima was observed using angioscopy. Based on the above results, we reduced the antiplatelet drug administration, and then the nephrectomy was performed. Ultimately, no cerebral infarction occurred in the perioperative or postoperative periods. Angioscopy allows for visual confirmation of thin neointima. If sufficient neointima can be confirmed, antiplatelet drug reduction can be performed more safely and reliably.